1990
DOI: 10.1590/s0034-89101990000600001
|View full text |Cite
|
Sign up to set email alerts
|

Assessment and prediction of asthma and its severity in the pediatric community

Abstract: Seventy four asthmatic children aged 7 to 11 years were examined along with controls matched by age and sex. Clinical and laboratory investigations preceded a 28-day follow-up where data about morning and evening peak expiratory flow rate (PEF), symptoms and treatment were recorded. The coefficient of variation of PEF was found to be an objective measurement of asthma severity that has statistically significant correlation with both symptoms (rs = .36) and treatment (rs = .60). Moreover, it separates mild and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

1993
1993
2008
2008

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 17 publications
1
5
0
Order By: Relevance
“…Essentially, children were diagnosed as asthmatic if they had wheezing with breathlessness in the last year. This one-year period prevalence of symptomatic asthma was found to be 12% which agrees with other recent surveys carried out in the Bristol area [12][13][14]. Seventy-five ofthe ^asthmatic' families had a repeat questionnaire administered 10 weeks after the first: 95% produced the same diagnosis.…”
Section: Methodssupporting
confidence: 90%
See 2 more Smart Citations
“…Essentially, children were diagnosed as asthmatic if they had wheezing with breathlessness in the last year. This one-year period prevalence of symptomatic asthma was found to be 12% which agrees with other recent surveys carried out in the Bristol area [12][13][14]. Seventy-five ofthe ^asthmatic' families had a repeat questionnaire administered 10 weeks after the first: 95% produced the same diagnosis.…”
Section: Methodssupporting
confidence: 90%
“…This permitted us to proceed with the entry criteria for the trial and eventually produce the 70 subjects for randomization (Table 1). .Analysis ofthe questionnaire responses used the formula previously applied [12,14] to establish the diagnosis of asthma. Essentially, children were diagnosed as asthmatic if they had wheezing with breathlessness in the last year.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly it was subsequently demonstrated that mite exposure increased the risk not only for asthma but also for atopic dermatitis [11]. We have also demonstrated that the severity of skin-test reactivity to house dust mite is an independent predictor of subsequent asthma severity [12]. The quantity of mite allergen in the household can apparently influence the likelihood of emergency admission of mite sensitive asthmatic children [6] and also increases the risk of readmission [7].…”
mentioning
confidence: 53%
“…Natural increase in mite allergen in houses has been related to the emergency admission of mite-sensitive asthmatic children, while similarly sensitive asthmatic controls whose house dust mite exposure was not increased do not relapse [19]. In addition, the presence and severity of the skin-prick test reaction to mites may be related to the subsequent asthma severity [20].…”
mentioning
confidence: 99%